Autoantibodies May Predict Immune-Related Toxicity: Results from a Phase I Study of Intralesional Bacillus Calmette–Guérin followed by Ipilimumab in Patients with Advanced Metastatic Melanoma - Da Gama Duarte, Jessica; Parakh, Sagun; Andrews, Miles C.; Woods, Katherine; Pasam, Anupama; Tutuka, Candani; Ostrouska, Simone; Blackburn, Jonathan M.; Behren, Andreas; Cebon, Jonathan (Frontiers in Immunology, 2018)
Immune checkpoint inhibitors (ICI) have revolutionized the treatment of advanced melanoma. The first ICI to demonstrate clinical benefit, ipilimumab, targets cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4), however long-term overall survival is just 22%. More than 40 years ago intralesional Bacillus Calmette-Guerin (BCG), a living attenuated strain of Mycobacterium bovis, was found to induce tumor regression by stimulating cell-mediated immunity following a localized and self-limiting infection. We evaluated these two immune stimulants in combination in melanoma with the aim of developing a more effective immunotherapy and to assess toxicity. In this phase I study patients with histologically confirmed stage III/IV metastatic melanoma received intralesional BCG injection followed by up to four cycles of intravenous ipilimumab (anti-CTLA-4) (ClinicalTrials.gov number NCT01838200). The trial was discontinued following treatment of the first five patients as the two patients receiving the escalation dose of BCG developed high-grade immune–related adverse events (irAEs) typical of ipilimumab monotherapy. These irAEs were characterized in both patients by profound increases in the repertoire of autoantibodies directed against both self- and cancer-antigens. Interestingly, the induced autoantibodies were detected at time points that preceded the development of symptomatic toxicity. There was no overlap in the antigen specificity between patients, and no evidence of clinical responses. Efforts to increase response rates through the use of novel immunotherapeutic combinations may be associated with higher rates of irAEs, thus the imperative to identify biomarkers of toxicity remains strong. While the small patient numbers in this trial do not allow for any conclusive evidence of predictive biomarkers, the observed changes warrant further examination of autoantibody repertoires in larger patient cohorts at risk of developing irAEs during their course of treatment. In summary: Dose escalation of intralesional BCG followed by ipilimumab therapy was not well tolerated in advanced melanoma patients and showed no evidence of clinical benefit. Measuring autoantibody responses may provide an early means for identifying patients at risk from developing severe irAEs during cancer immunotherapy.